Blood donor biobank suitability for identifying carriers with disease associated variants enriched in Finland - Vaittinen, Eevaleena (My University, 2022)
Biobanks collect samples from donors for medical research. Blood Service Biobank consists of samples from healthy enough blood donors, and it is assumed to be useful source for population and health studies because of the readily available sample collections. To understand better the actual usefulness of the blood donor biobank in genetic studies, in this study we have evaluated frequencies and geographical distributions of common and rare genetic variants in the Finnish population. The isolated population of Finland due to the bottleneck effect and the small founder population offers the opportunity to study genetic susceptibility variants that are rare in other populations. Finland has developed its own disease heritage, which consists of a group of recessive diseases that are more common in Finland compared to the rest of Europe. The population of a few thousand individuals settled mainly in the South and less in the East and the West. Another phenomenon that affected Finland's gene pool was the colonization of Northern/Eastern Finland from Southern Finland in the 15th-16th centuries by small families. The Finnish population has favorable characteristics for genetic research, such as general homogeneity, reduced diversity and increased linkage disequilibrium. The purpose of this Master of science project is to investigate how well blood donor Biobank can be used for identifying carriers with rare disease associated variants enriched in Finland In this study 35 400 blood donors’ genomic data was used for identifying the carriers of 51 disease susceptibility variants enriched in Finland among healthy blood donors. Allele frequencies for the variants were calculated based on number of heterozygotes and homozygotes. The allele frequencies of the SPR Blood Service Biobank were compared with two other Finnish datasets and one non-Finnish dataset. Blood donors’ postal code information was combined with the genomic data and allocated to the right province based on the post code. This way we were able to compare variant distribution between 19 Finnish provinces Results show that all of the investigated variants can be found among blood donors. Statistical tests showed significant differences in variant prevalence between East and West. Some of variants showed differences between provinces. Based on the study, it can be concluded that the Blood Service Biobank is well suited for finding rare disease associated variants among blood donors.